Study on Role of Radio for Rural Education in Pakistan - Jumani, Nabi Bux (2009)
It was found that the majority of the listeners possessed radio sets and was getting benefit from the educational programmes of radio. The programmes were informative and motivating. The strategies of radio for rural education were appreciable because these infused mobility, widened horizon of rural people and focused attention on the goals and problems of rural people. It could be used to enhance literacy (through distance and non-formal education). The producers/comperes were found keenly interested in their job. It was revealed that priority was given to education and rural development programmes of radio. Programmes needed detail and summary at the end. Furthermore language was not easy. Mobile radio station was needed for rural educational programme to cater to the needs of far flung areas. School broadcast (distance and non-formal teaching) was the need of the day. Social workers/opinion leaders opined that there was need of developing self reliance. Radio provides guidance to rural people in solving the problems of rural development. They felt the need of starting school broadcasting. Radio was being utilized for apprising villagers with their problem. There was need of maintaining more educational programmes. Rural programmes were to be in mother tongue. It was recommended that for educational purposes Radio Pakistan and AIOU may produce programmes which have their strong links/roots in the surroundings of the rural people. Radio schools like Interactive Radio instruction (IRI) may be used for effective teaching learning process in rural areas. Time of educational programmes should be enhanced. Programmes like radio rural forum may be started as well as open broadcasting should be adopted for rural development programme. (Contains 5 tables.)
ISSN: 1302-6488 Issue: 4 Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:6QWQ77L4 2405685:H456VCTC
Keywords: Distance Education; Educational Technology; Foreign Countries; Instructional Effectiveness; Nonformal Education; Radio; Rural Areas; Rural Development; Rural Education; Teaching Methods

Evaluating large‐scale interactive radio programmes - Potter, Charles; Naidoo, Gordon (Distance Education, 2009)
This article focuses on the challenges involved in conducting evaluations of interactive radio programmes in South Africa with large numbers of schools, teachers, and learners. It focuses on the role such large‐scale evaluation has played during the South African radio learning programme’s development stage, as well as during its subsequent sustained implementation phase. The model evolved for evaluation of interactive radio instruction is based within the context of a shoestring/real‐world evaluation tradition, where funding for internal evaluation has been limited over the period of the programme’s development to scale, necessitating focused use of resources in a longitudinal evaluation design. The evaluation approach is participatory and multimethod, linking the requirements of external summative evaluation conducted for accountability, with data yielded by internal (formative and developmental) evaluation. This is done through internal and formative evaluative studies of limited scope, combined with developmental classroom‐based evaluation based on the logic of project team members working with teachers to promote the programme’s self‐evaluative capacity.
Publisher: Routledge _eprint: https://doi.org/10.1080/01587910902845980 shortDOI: 10/ct47qx KerkoCite.ItemAlsoKnownAs: 10/ct47qx 2339240:RS87K3HC 2405685:62Z6BK9N
Keywords: distance education; interactive radio instruction; large‐scale implementation; modalities; pedagogy; programme evaluation; shoestring/real‐world evaluation

Tuned in to Student Success: Assessing the Impact of Interactive Radio Instruction for the Hardest-To-Reach - Ho, Jennifer; Thukral, Hetal (Education Development Center, 2009)
This study reviews student assessment data collected from 15 EDC projects to determine the impact of interactive radio instruction (IRI) on student achievement in hard-to-reach areas.
KerkoCite.ItemAlsoKnownAs: 2339240:4A5246Z6 2339240:62K8ZTKG 2339240:J5GYXMFY 2405685:V73WF7EZ 2405685:VF7IM4CW 2405685:WH7JDBUP
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Radio Instruction to Strengthen Education (RISE) in Zanzibar. Learning gains assessment: more than child's play. - Morris, Emily; Philip, Miriam; Othman, Abrahman Faki; Mitchell, James; Quiones, Esteban J.; Leatxe, Denisse (Education Development Center, Inc. and Ministry of Education and Vocational Training, 2009)
Students at a RISE learning center, who now have access to an early childhood education. RADIO INSTRUCTION TO STRENGTHEN EDUCATION (RISE) IN ZANZIBAR LEARNING GAINS ASSESSMENT:…
KerkoCite.ItemAlsoKnownAs: 2339240:B9UUQVJH 2405685:9E3KIGN5

Tuned In To Student Success Assessing the Impact of Interactive Radio Instruction for the Hardest-to-Reach - Ho, J.; Thukral, H.; Laflin, M. (2009)
A review of recent research was conducted to assemble evidence on the impact that Interactive Radio Instruction (IRI) may have on improving student learning outcomes. IRI is an instructional tool designed to deliver a family of active learning packages via radio broadcast using a dual-audience approach. IRI exposes students to regular, curriculum-based learning content while modeling effective learning activities and classroom organization techniques for teachers. As IRI continues to be called upon to improve teaching and learning in low-resource and hard-to-reach areas, a better understanding of the empirical data available is critical to guide the way forward. IRI has been implemented by Education Development Center, Inc. (EDC) in over 50 countries over the past 30 years. This paper is a review of existing student and teacher data collected by EDC’s IRI projects. Effect sizes are used to summarize what is known about the effect of IRI on student learning gains in Grades K-4 for English, Mathematics, Science, Social Studies, and Local Language. In all, student test results from 13 projects, ranging from Nicaragua in 1977 through Indonesia in 2008, are reviewed, as are teacher observation outcomes from Mali and Madagascar.
KerkoCite.ItemAlsoKnownAs: 2339240:QXWFNRPL 2405685:X87WD2EZ
Keywords: ⛔ No DOI found

Tuned in to Student Success, Assessing the impact of Interactive Radio Instruction for the hardest-to-reach - Ho, Jennifer; Thukral, Hetal (Journal of Education for International Development, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:C9UYYZTE 2339240:SX76SLEZ 2405685:5TDGEFV4 2405685:6LNNLS62 2405685:LQEM4ZCI 2534379:58BVKHVC
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Tuned in to Student Success: Assessing the Impact of IRI - Education Development Center, Inc. (2009)
This study reviews student assessment data collected from 15 EDC projects to determine the impact of interactive radio instruction (IRI) on student achievement in hard-to-reach areas.
KerkoCite.ItemAlsoKnownAs: 2339240:RXJXAI35 2405685:JCHFPDXZ

The gender digital divide in rural Pakistan: How wide is it and how to bridge it? - Siegmann, K. A. (2009)
textabstractWhile Pakistan’s National Information Technology (IT) Policy aims at harnessing the potential of information and communication technologies (ICTs) for development, especially in the underserved rural areas, it ignores the role of existing gender inequalities on the possible benefits of ICTs. We have investigated aspects of the ‘gender digital divide’ in rural areas of Pakistan in order to enable an evidence-based gender-sensitive revision of the policy as well as ICT-related interventions from which both females and males gain. The study took place in four of the most marginalized rural districts of the country where this divide is likely to be most pronounced. We found mobile phones to be the ICT that is most commonly available in rural Pakistan. Radios and TV sets are the second most widespread technologies in marginalised rural areas. However, mobile sets at hand are largely owned by women’s husbands, fathers and brothers, whose permission to make calls is required by a large share of all female respondents. I, therefore, argue that availability and gendered use of ICTs are two different things altogether. Social norms related to women and girls’ access to education as well as regulating their mobility prevent them from using ICTs. These norms have to be taken into account in policies and interventions to ensure women and girls’ access to and beneficial use of ICTs.
KerkoCite.ItemAlsoKnownAs: 2339240:G8SKSDEL 2405685:8D4Z2825